How do website-based presentation Tools Impact The Enhancement of Digital Literacy comprehension? Integration with blended learning - Guspriadi, Yan; Firman, Firman; Amat, Muhammad Asyraf Bin Che (Jurnal Aplikasi IPTEK Indonesia, 2024)
Technology offers significant contributions and advantages. During a global pandemic, the education sector is particularly advantaged by the utilization of technology. This study seeks to evaluate the efficacy of employing information services through the blended learning approach in enhancing students' comprehension of digital literacy amidst the pandemic. This study used a Quasi-Experimental methodology utilizing a Non-Equivalent Control Group design. The study population consisted of students in the twelfth grade, and a purposive sampling method was employed to choose participants from class XII A. The main focus of the study was to assess the student's level of comprehension in the field of digital literacy. The utilization of interactive media in service implementation specifically enhances digital literacy comprehension, resulting in a significant gain in knowledge